1979
DOI: 10.1203/00006450-197907000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Aspects of Renal β-Amino Acid Transport II. Ontogeny of Uptake and Efflux Processes and Effect of Anoxia

Abstract: SummaryRenal cortex slices from newborn, tweek, and 4-week-old Sprague-Dawley rats had reduced initial rates of taurine uptake compared io adult slices after short (< 30 min) incubation periods. From birth onward, steady-state accumulation occurred by at least two sodium-dependent uptake systems. The first system had an "apparent KmlW = 0.1 mM and a Vmax varying from 1.8 to 5.1 pmoles/ml ICF/120 min at four ages. The second uptake mode had an apparent Kmz = 12-16 mM and a Vmax of 45 pmoles/ml ICF/120 min. Emux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…(Pediatr Res 22: 163-167,1987) Immature animals of virtually all mammalian species have a "physiologic" generalized aminoaciduria which results in excretion of a higher fraction of the filtered amino acid load of all amino acid classes (1,2). Our laboratory has focused on physiologic factors that modify the development of amino acid transport systems in order to better understand the processes by which these transport sites achieve a mature transport profile (3)(4)(5)(6)(7). For an appropriate transport probe , we have used the l3-amino acid taurine, since it is relevant in the nutrition of young animals (8) and since one can manipulate the dietary level of sulfur amino acids to alter the renal handling of taurine (5,(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…(Pediatr Res 22: 163-167,1987) Immature animals of virtually all mammalian species have a "physiologic" generalized aminoaciduria which results in excretion of a higher fraction of the filtered amino acid load of all amino acid classes (1,2). Our laboratory has focused on physiologic factors that modify the development of amino acid transport systems in order to better understand the processes by which these transport sites achieve a mature transport profile (3)(4)(5)(6)(7). For an appropriate transport probe , we have used the l3-amino acid taurine, since it is relevant in the nutrition of young animals (8) and since one can manipulate the dietary level of sulfur amino acids to alter the renal handling of taurine (5,(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Indeed, in some time course experiments, the initial (1-and 2-min) uptake was more brisk in tubules from the young animals. The differences are observed in our previous studies (12,18) would indicate that the efflux of taurine out of the slice or isolated tubule is impaired in immature animals. Since efflux is presumably occurring at the basolateral membrane surface, studies of transport differences in isolated basolateral membrane would appear to be important.…”
Section: Discussionmentioning
confidence: 49%
“…The mechanism of neonatal taurinuria in slices (1 2) and tubules (18) appears to involve a decreased initial rate of uptake with a reduction in the V,,, of taurine accumulation. A third mechanism, decreased efflux at the basolateral membrane in immature cortex, also appears to be relevant (2,3,10,12,18,33), but the kinetic characteristics of this diminished rate of exit are not clear. Finally, changes in "effective intravascular volume" may influence the transport of organic solutes (2 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the renal adaptive response to changes in sulfur amino acid intake is found in the brush border membrane, but the urinary excretion pattern is only partially adapted. It is possible that delayed emux of taurine across the basolateral surface accounts for this excessive taurinuria, since our previous studies have indicated reduced basallateral efflux in immature rats (4,6,7).Although the adaptive response has been shown to partially exist in terms of urinary excretion and to fully exist at the apical surface in 28-day-old rats, little is known about the response in nursing animals at this membrane surface. Herein we describe the influence of the altered amino acid diets fed to the mothers of nursing rats on the renal handling and brush border accumu-…”
mentioning
confidence: 95%
“…Thus, the renal adaptive response to changes in sulfur amino acid intake is found in the brush border membrane, but the urinary excretion pattern is only partially adapted. It is possible that delayed emux of taurine across the basolateral surface accounts for this excessive taurinuria, since our previous studies have indicated reduced basallateral efflux in immature rats (4,6,7).…”
mentioning
confidence: 99%